Daerah Jelajah dan Penggunaan Ruang Kukang Jawa (Nycticebus javanicus) Di Taman Nasional Gunung Halimun Salak, Jawa Barat - ARISMAYANTI, EKA; PERWITASARI, RR DYAH; WINARTI, INDAH (Departemen Biologi, Institut Pertanian Bogor, 2018)
Javan slow loris (Nycticebus javanicus) is a slow moving nocturnal prosimian primate. Javan slow lorises are considered critically endangered by International Union for the Conservation of Nature. To date, there is limited source information available regarding wild loris ecology and behavior. In this study, home range areas and use space of wild Javan slow loris was carried out in Mount Halimun-Salak National Park. This study aims to measure home range size and to analyze activity budgets in natural forest conditions. Kernel Home Range methods were used to analyze home range areas, while Point Centered Quarter methods were used to collect habitat data, and five minute Instantaneous-Focal Animal Sampling was used to observe and record behavioral data. Two adult female lorises were observed. Analysis showed contiguous home range sizes of 5.43 and 5.58 hectares for Individuals I and II, respectively. These home ranges were larger than that reported in Malaysian Nycticebus coucang. Behavioral analysis showed that daily activities were dominated by travel, feeding, active, and foraging, which took place primarily in the lower canopy stratum, whereas sleeping typically occurred in the medium canopy stratum. The use of space of Javan slow loris correlated with height, substrat, contact, and size of branch.